Delivering HIV services in partnership: factors affecting collaborative working in a South African HIV programme. Issue 1 (December 2017) - Jobson, Geoffrey; Grobbelaar, Cornelis; Mabitsi, Moyahabo; Railton, Jean; Peters, Remco; McIntyre, James; Struthers, Helen
Abstract Background The involvement of Global Health Initiatives (GHIs) in delivering health services in low and middle income countries (LMICs) depends on effective collaborative working at scales from the local to the international, and a single GHI is effectively constructed of multiple collaborations. Research is needed focusing on how collaboration functions in GHIs at the level of health service management. Here, collaboration between local implementing agencies and departments of health involves distinct power dynamics and tensions. Using qualitative data from an evaluation of a health partnership in South Africa, this article examines how organisational power dynamics affected the operation of the partnership across five dimensions of collaboration: governance, administration, organisational autonomy, mutuality, and norms of trust and reciprocity. Results Managing the tension between the power to provide resources held by the implementing agency and the local Departments' of Health power to access the populations in need of these resources proved critical to ensuring that the collaboration achieved its aims and shaped the way that each domain of collaboration functioned in the partnership. Conclusions These findings suggest that it is important for public health practitioners to critically examine the ways in which collaboration functions across the scales in which they work and to pay particular attention to how local power dynamics between partner organisations affect programme implementation.